Synthesis, physical, optical, structural and radiation shielding characterization of borate glasses: A focus on the role of SrO/Al2O3 substitution. Issue 2 (15th January 2022) - Ahmed, Mohamad Raheem; Sekhar, K. Chandra; Ahammed, Sheik; Sathe, Vasant; Alrowaili, Z.A.; Amami, Mongi; Olarinoye, I.O.; Al-Buriahi, M.S.; Tonguc, B.T.; Shareefuddin, Md.
Abstract: In a bid to expand the amount of information available on glass systems and their potential applications for radiation shielding design, glass samples with the compositions (30-x)SrO-xAl2 O3 –68B2 O3 –2V2 O5 (x = 5, 7.5, 10, 12.5&15 mol %) coded as SABV0 - 4 were prepared by the melt-quenching technique and analyzed for their optical, structural, physical, and radiation shielding features. The glassy (amorphous) nature of the SABV glass samples was affirmed by broad peaks of X-ray diffraction spectra. Calculated values of density and molar volume shown opposite behavior and the variation of these values were discussed as structural modifications in the glass matrix. From recorded optical absorption spectra optical band gap energy (Eg)-indirect transition, Urbach energy and optical basicity were estimated. FTIR spectra were recorded for all the samples in the range 400 cm −1 to 4000 cm −1 . The FTIR absorbance spectra unveiled the SABV network structure mainly incorporating of BO3 and BO4 units. Raman spectroscopy is achieved to detect the structural changes and at higher wavenumber, B–O stretching modes in [BO3 ] observed with one or two NBO's. The results of ESR spectra of glasses have indicated the highly covalent environment of vanadium ions. Analysis of the photon shielding parameters of the glasses which were obtained primarily from FLUKA Monte Carlo simulations and XCOM computations revealed photon energy and glass chemical composition dependence. The mass attenuation coefficient and effective atomic number ranged from 0.2668 to 0.3385 cm 2 g -1 and 12.98–15.93 accordingly as the weight fraction of Sr increased from 16.06 to 26.72% in the glasses. Generally, photon shielding ability of the SABV glasses follows the trend: SABV0 > SABV1 > SABV2 > SABV3 > SABV4. The thermal neutron total cross section follows the same trend with values fluctuating between 71.9553 and 80.6268 cm −1 . However, SABV1 showed superior fast neutron moderating capacity among the glasses. The present SABV glasses showed outstanding photon shielding ability compared to common shields. The prepared glasses are thus suitable candidates for radiation protection applications.